2006
DOI: 10.1002/chem.200600011
|View full text |Cite
|
Sign up to set email alerts
|

α‐Carbonyl Substituent Effect on the Lifetimes of Triplet 1,4‐Biradicals from Norrish‐Type‐II Reactions

Abstract: Triplet 1,4-biradicals were generated by Norrish-Type-II hydrogen transfer from alpha-heteroatom-substituted beta-branched butyrophenones 1-6 and detected by laser flash absorption measurements. For three oxy-substituted compounds 2-4 (R(alpha)=OH, OCOMe, OCOOEt) comparable lifetimes were determined in acetonitrile (roughly 1.5 micros). In benzene, divergent trends were observed: for the hydroxy compound 2 a lower lifetime of 790 ns was determined, whereas for 3 and 4 the lifetimes increased to 4.9 micros. Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…TR-IY studies on gas-phase EF by Rodrigues et al revealed a tri-exponential decay involving a long-lived, > 900 ps component, which was assigned to long-lived triplet states 59 . Apart from excited triplet state reactions such as singlet oxygen sensitising, the existence of such triplet states could be particularly problematic in sunscreen formulation since aromatic carbonyl compounds are known to undergo fragmentation reactions from their triplet states, rather than phosphorescence to the ground state 67,68 . However, as previously discussed and as observed in the studies by Horbury et al on EF in solution, solvent effects -even those of the weakly perturbing cyclohexane -allow for photoisomerisation relaxation pathways to become accessible in EF, justifying its use in sunscreen formulations 36 .…”
Section: Solvent (Solution Vs Vacuum)mentioning
confidence: 99%
“…TR-IY studies on gas-phase EF by Rodrigues et al revealed a tri-exponential decay involving a long-lived, > 900 ps component, which was assigned to long-lived triplet states 59 . Apart from excited triplet state reactions such as singlet oxygen sensitising, the existence of such triplet states could be particularly problematic in sunscreen formulation since aromatic carbonyl compounds are known to undergo fragmentation reactions from their triplet states, rather than phosphorescence to the ground state 67,68 . However, as previously discussed and as observed in the studies by Horbury et al on EF in solution, solvent effects -even those of the weakly perturbing cyclohexane -allow for photoisomerisation relaxation pathways to become accessible in EF, justifying its use in sunscreen formulations 36 .…”
Section: Solvent (Solution Vs Vacuum)mentioning
confidence: 99%
“…28 Subsequent trapping experiments and electron-transfer experiments involving the intermediate 1-hydroxy-1,4-biradicals, and eventually transient absorption spectroscopy, 29 established these species in the nano-to microsecond lifetime regime. 30,31 In order to release diverse structure families, the basic Norrish II substrates (that are able to produce alkenes (a) beside the primary enols) have to be tuned to the desired products by introducing further functional groups that lead to the formation of aldehydes (b), Michael ketones (c) or α,β-unsaturated carboxylic acid derivatives (d) (Scheme 2).…”
Section: Scheme 1 Norrish II Carbonyl Photochemistry Involving Triplementioning
confidence: 99%
“…The three golden routes and three examples of photocages(33,31,36) that realize these concepts Cet + Br -: 35A. G. Griesbeck et al…”
mentioning
confidence: 99%
“…[14] In view of this, understanding of the factors that influence the lifetimes of triplet 1,4-biradicals (t BR ), which are also intermediates in reactions, such as Paterno-Büchi and enoneolefin photocycloadditions, [15] and their behavior [16] continues to be of significant contemporary interest. [17] Insofar as…”
Section: Introductionmentioning
confidence: 98%